The Productive Waqf as an Alternative Solution to Poverty Eradication in Indonesia - Zamzami, M. Khotimi; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The Poverty remains a persistent socio-economic challenge in Indonesia, exacerbated by the Covid-19 pandemic and rising fuel prices. Despite numerous government and private-sector interventions, poverty reduction efforts have yielded limited long-term impact. This paper examines the potential of productive waqf as an Islamic philanthropic instrument for sustainable poverty alleviation. With over 420 thousand hectares of waqf land and an estimated cash waqf potential of Rp180 trillion, Indonesia possesses significant untapped resources that can be mobilized for economic empowerment. The study demonstrates that when managed professionally, productive waqf can serve as a catalyst for generating sustainable income, creating employment opportunities, and strengthening micro, small, and medium enterprises (MSMEs). However, it also identifies critical challenges that hinder its optimal implementation, including regulatory inconsistencies, limited institutional capacity, and low public awareness. The primary contribution of this research lies in proposing a practical and integrative model for optimizing productive waqf as a tool to support poverty alleviation and promote inclusive economic growth in Indonesia.